Effects of intermittent hypobaric hypoxic exercise on cardiovascular adaptations - Futoshi Ogita (Japanese Society of Physical Fitness and Sports Medicine, 2013)
We examined the effects of acute and chronic exercise under hypobaric hypoxia on cardiovascular responses/adaptations to test the hypothesis that cardiovascular adaptations are more effective after exercise under hypobaric hypoxia than under normobaric normoxia. First, we found that a decrease in peripheral resistance and blood pressure (BP) concomitant with an increase in stroke volume (SV) and cardiac output (CO) could be more effectively induced by chronic exercise under hypobaric hypoxia, than under normoxia. Also, the decrease in peripheral resistance and BP might be attributable to a decrease in arterial stiffness and enhanced vasodilatory activity. Second, the effects of acute hypoxic exposure and exercise on arterial stiffness and vasodilatory activity were examined. Arterial stiffness decreased after acute exercise alone, but not after acute hypoxic exposure alone. However, vasodilatory activity was enhanced by hypoxic stimulus, and to greater extent after hypoxic exercise. These findings suggested that stimulation with concomitant exercise and hypoxia could bring about more beneficial vascular responses. Finally, the time course of cardiovascular adaptations to hypobaric hypoxic exercise were accessed, and we found that a significant decrease in BP, accompanied by an increase in SV and CO, occurs within one week of starting the exercise; and that there is a significant decrease in arterial stiffness by the end of the second week. These changes in cardiovascular responses persisted until the end of the training period. Our findings suggest that exercise under hypobaric hypoxia brings about more rapid and effective beneficial cardiovascular adaptations than that under normoxia.